Discovery of histone deacetylase 3 (HDAC3)-specific PROTACs() - Xiao, Yufeng (Chem Commun (Camb), 2020)
Histone deacetylases (HDACs) are validated drug targets for cancer treatment. Increased HDAC isozyme selectivity and novel strategies to inhibit HDAC activity could lead to safer and more effective drug candidates. Nonetheless, it is quite challenging to develop isozyme-specific HDACi due to the highly conserved catalytic domain. We discovered XZ9002, a first-in-class HDAC3-specific PROTAC that potently degraded HDAC3. Importantly, XZ9002 is more effective to inhibit cancer cell proliferation than its proteolysis-inactive counterpart, suggesting HDAC3 degradation is a novel and promising anticancer approach.